A life in the struggle : Ivory Perry and the culture of opposition - Lipsitz, George (Critical perspectives on the past., 1995)
Now updated to include the final chapter of Ivory Perry's life, this new edition completes the life story of the grass-roots activist whose flamboyant direct action protests and patient behind the scenes organizing helped educate and agitate his community in the struggle for civil rights and economic opportunity.